Design of a multi criteria decision model-fuzzy analytical hierarchy approach - Sona, P.; Johnson, T.; Vijayalakshmi, C. (International Journal of Engineering and Technology, 2017)
In Supply Chain Management(SCM),vendor selection has become a very important activity. By selecting the appropriate vendor, companies can avoid barriers and do for efficient production. The aim of this paper is to identify the important criteria that may develop strategies of the organizations. It deals with the analysis of vendor selection problem using Fuzzy Analytical Hierarchy Process (FAHP).The comparison has made between the parameters criteria and alternatives by designing a model of uncertainty. The proposed method has applied in an automobile industry to choose their vendors in a best way.